Mobile Robot to Assist in Therapies for Children with Autism - Taype Mateo, Madai Keila (2021)
The increase in the autistic population and rapid technological advances have led to further research on robot-assisted rehabilitation for autism therapy as a practical system aimed at overcoming the distance between autistic patients and their therapists. In this investigation, an interactive mobile robot was developed whose main objective is to perform therapy for children with autism spectrum disorder (ASD) that meets certain qualities that Will be chosen by the therapist, so that the robot Will be able to give treatment in different approaches of language, speech, and coordination. This mobile robot offers the ease of being manipulated by a geomagnetic router (GRG) glove, RFID cards that allow the display of different expressions (emotions), and SD cards that can sabe voice recordings or songs according to the therapist